Preparation method of in-situ cured lithium battery and in-situ cured lithium battery
By adding fluorinated alkyl modified polymer monomers during the negative electrode slurrying process and adding a small amount of initiator to the electrolyte to form a semi-solid electrolyte, the problems of increasing viscosity and lower conductivity of the electrolyte are solved, and the rate performance and high-temperature performance of the battery are improved.
Patent Information
- Application Number
- CN202411726692.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
When the existing gel electrolyte preparation method forms a gel-like semi-solid electrolyte, it leads to an increase in the viscosity of the electrolyte and a decrease in the ionic conductivity, which in turn affects the rate performance and high-temperature performance of the battery.
During the negative electrode slurrying process, fluorinated alkyl-modified polyamide monomer or polyacrylate monomer is added, and a small amount of initiator is added to the electrolyte to form a semi-solid electrolyte through in-situ thermal polymerization to avoid the problem of increasing viscosity and reducing conductivity of the electrolyte.
It significantly improves the application efficiency and in-situ curing uniformity of gel semi-solid electrolytes, and improves the high-temperature performance of the battery while not degrading the rate performance.
Smart Images

Figure BDA0005159377320000021 
Figure BDA0005159377320000022 
Figure BDA0005159377320000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a preparation method of an in-situ cured lithium battery and an in-situ cured lithium battery. Background Art
[0002] With the widespread application of lithium-ion batteries in portable electronic devices, electric vehicles and energy storage systems, improving the safety and stability of batteries has become a research focus. Although liquid electrolytes have high ionic conductivity and good wettability, they have problems such as leakage risk, poor thermal stability and flammability, which limit their use in applications with high safety requirements. In contrast, semi-solid gel electrolytes significantly improve the mechanical strength of the electrolyte by introducing a polymer network structure, effectively reducing the risk of leakage and the possibility of thermal runaway. In addition, gel electrolytes also have good flame retardancy and thermal stability, and can maintain structural integrity under high temperature environments. The research results show that gel electrolytes are an ideal choice for the development of high-performance lithium-ion batteries in the future, providing a new direction for achieving safer and more reliable energy storage systems.
[0003] The current mainstream gel electrolyte is formed by adding polymerizing monomers, crosslinking agents and initiators to the liquid electrolyte, thermally polymerizing it under high temperature and high pressure to form a gel-like semi-solid electrolyte in situ. This method will increase the viscosity of the liquid electrolyte itself and reduce its ionic conductivity. As the viscosity of the electrolyte increases, the wettability will also decrease, resulting in poor electrode-electrolyte contact interface, and the interface uniformity and battery consistency of the semi-solid battery produced will be unstable.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing an in-situ cured lithium battery and an in-situ cured lithium battery, aiming to avoid the problems of increased electrolyte viscosity and reduced conductivity when forming a gel electrolyte, thereby improving the rate performance and high temperature performance of the battery.
[0006] The present invention is achieved in that:
[0007] In a first aspect, the present invention provides a method for preparing an in-situ solidified lithium battery, comprising:
[0008] Providing positive electrode sheets, separators and electrolytes containing initiators;
[0009] A negative electrode active material, a conductive agent, a binder and a polymerizable monomer are mixed to obtain a negative electrode slurry, and the negative electrode slurry is coated on a negative electrode current collector and dried to prepare a negative electrode plate; wherein the polymerizable monomer is a fluorinated alkyl modified polyamide monomer or a fluorinated alkyl modified polyacrylate monomer;
[0010] Assembling the negative electrode sheet, the positive electrode sheet and the separator to obtain a battery cell;
[0011] The electrolyte is injected into the battery cell, and after formation, the temperature is raised and polymerized.
[0012] In an optional embodiment, the general formula of the fluorinated alkyl modified polyamide monomer is:
[0013]
[0014] In the formula, R is a fluoroalkyl group, and the carbon atom content in R is 1 to 20; 2≤n1≤10, 1≤n2≤20;
[0015] Preferably, R is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-.
[0016] In an optional embodiment, the general formula of the fluorinated alkyl modified polyacrylate monomer is:
[0017]
[0018] In the formula, R1 is a fluoroalkyl group, and the carbon atom content in R1 is 1 to 20; R2 is H or CH3-, 1≤n≤20;
[0019] Preferably, R1 is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-.
[0020] In an optional embodiment, when preparing the negative electrode slurry, the mass fraction of each raw material is as follows: negative electrode active material 94%-97%, conductive agent 1.5%-2.5%, binder 1.0%-2.3% and polymerized monomer 0.3%-1.6%.
[0021] In an alternative embodiment, the negative electrode active material is graphite;
[0022] and / or, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene;
[0023] And / or, by mass fraction, the binder includes 0.5%-1.5% carboxymethyl cellulose, 0%-1.3% polyacrylic acid and 0.2%-0.8% styrene-butadiene rubber;
[0024] And / or, the preparation process of the negative electrode slurry includes: firstly mixing carboxymethyl cellulose, polyacrylic acid and water to obtain a glue solution, then mixing the glue solution with a conductive agent and a negative electrode active material in sequence, and then mixing with styrene-butadiene rubber and a polymerized monomer;
[0025] And / or, the negative electrode current collector is a copper foil with a thickness of 4 μm-12 μm;
[0026] And / or, the coating double-sided density of the negative electrode slurry is 100-300g / m 2 .
[0027] In an optional embodiment, the mass fraction of the initiator in the electrolyte is 0.05%-2.0%, the mass fraction of the basic lithium salt electrolyte is 98-99.95%, and the basic lithium salt electrolyte contains 1%-3% of an unsaturated olefinic additive;
[0028] And / or, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dicumyl peroxide and benzoyl peroxide.
[0029] In an optional embodiment, the basic lithium salt electrolyte includes a lithium salt, a solvent and an additive;
[0030] Preferably, the lithium salt is LiPF6, and the concentration of the lithium salt is 0.8 mol / L-1.2 mol / L;
[0031] Preferably, the additive includes vinylene carbonate and propylene sulfite, the mass fraction of vinylene carbonate is 0.8%-1.2%, and the mass fraction of propylene sulfite is 1.5%-2.5%;
[0032] Preferably, the solvent comprises ethylene carbonate and ethyl methyl carbonate, and the volume ratio of ethylene carbonate to ethyl methyl carbonate is (2-4):(6-8).
[0033] In an optional embodiment, during the temperature-raising polymerization, the polymerization temperature is controlled to be 45° C.-60° C., and the polymerization time is 6 h-8 h;
[0034] And / or, the formation temperature is 20°C-30°C.
[0035] In an optional embodiment, the preparation process of the positive electrode sheet includes: mixing a positive electrode active material, a conductive agent and a binder to obtain a positive electrode slurry, applying the positive electrode slurry on a positive electrode collector and drying to obtain a positive electrode sheet;
[0036] Preferably, when preparing the positive electrode slurry, the mass proportion of the positive electrode active material is 96.8%-97.3%, the mass proportion of the conductive agent is 1.8%-2.2%, and the mass proportion of the binder is 0.8%-1.2%;
[0037] Preferably, the positive electrode active material is selected from at least one of lithium iron phosphate, ternary nickel cobalt manganese, lithium manganese iron phosphate, lithium nickel manganate and lithium manganate;
[0038] Preferably, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene;
[0039] Preferably, the binder is selected from at least one of polyvinylidene fluoride, polyacrylic acid and polyacrylonitrile.
[0040] In a second aspect, the present invention provides an in-situ solidified lithium battery prepared by any one of the preparation methods in the aforementioned embodiments.
[0041] The present invention has the following beneficial effects: in the process of negative electrode slurrying, a fluorinated alkyl-modified polyamide monomer or a fluorinated alkyl-modified polyacrylate monomer that is relatively stable to water and oxygen is added, and the H atoms in the polyamide monomer or the polyacrylate monomer are replaced by the fluorinated alkyl group, so that the chemical stability of the polymer is significantly improved, and it is not easy to be hydrolyzed or oxidized when added during the negative electrode slurrying, and a small amount of initiator is subsequently added to the electrolyte to form a semi-solid electrolyte by in-situ thermal polymerization. The method provided by the present invention only adds a small amount of initiator to the electrolyte, avoiding the problem of increased viscosity and reduced conductivity of the electrolyte when the monomer and initiator are added to the electrolyte together during the preparation of the electrolyte in the traditional scheme; it can also avoid premature polymerization during transportation or long-term storage, thereby significantly improving the application efficiency and in-situ curing uniformity of the gel semi-solid electrolyte, and improving the high temperature performance of the battery while not degrading the rate performance. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0043] The present invention creatively adds a special type of polymerizable monomer into the negative electrode slurry, adds an initiator into the electrolyte, and forms a semi-solid electrolyte through in-situ thermal polymerization. The embodiment of the present invention provides a method for preparing an in-situ solidified lithium battery, and the steps are as follows:
[0044] S1. Provide negative electrode sheet
[0045] The negative electrode active material, conductive agent, binder and polymerized monomer are mixed to obtain negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector and dried to prepare the negative electrode plate. In the process of negative electrode slurry, a specific type of polymerized monomer that is relatively stable to water and oxygen is added to avoid premature contact between the polymerized monomer and the initiator, and to prevent premature polymerization during transportation or long-term storage, thereby significantly improving the application efficiency and in-situ curing uniformity of the gel semi-solid electrolyte; only a small amount of initiator needs to be added to the electrolyte to avoid the problem of increased electrolyte viscosity and reduced conductivity.
[0046] The polymerizable monomer is a fluorinated alkyl-modified polyamide monomer or a fluorinated alkyl-modified polyacrylate monomer, preferably a fluorinated alkyl-modified polyamide monomer, which can further improve the rate performance and high temperature performance of the battery.
[0047] Furthermore, the general formula of the fluorinated alkyl-modified polyamide monomer is:
[0048]
[0049] In the formula, R is a fluoroalkyl group, and the carbon atom content in R is 1 to 20, such as 1, 3, 5, 8, 10, 13, 15, 18, 20, etc. Preferably, R is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-, and R can be any of the above groups.
[0050] In the formula, 2≤n1≤10, n1 can be 2, 3, 4, 5, 6, 7, 8, 9, 10, etc.; 1≤n2≤20, n2 can be 1, 3, 5, 8, 10, 13, 15, 18, 20, etc.
[0051] It should be noted that by introducing fluorinated alkyl groups into polyamide monomers which have excellent chemical stability, the strong electronegativity of fluorine atoms can significantly improve the chemical stability of the polymer, so that it will not be hydrolyzed or oxidized when added during the negative electrode slurry.
[0052] Furthermore, the general formula of the fluorinated alkyl modified polyacrylate monomer is:
[0053]
[0054] In the formula, R1 is a fluoroalkyl group, and the carbon atom content in R1 is 1 to 20, such as 1, 3, 5, 8, 10, 13, 15, 18, 20, etc. Preferably, R1 is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-, and R1 can be any of the above groups.
[0055] In the formula, R2 is H or CH3-, and R2 can be any of the above groups. 1≤n≤20, and n can be 1, 3, 5, 8, 10, 13, 15, 18, 20, etc.
[0056] Furthermore, when preparing the negative electrode slurry, the mass fractions of the raw materials are as follows: 94%-97% of the negative electrode active material, 1.5%-2.5% of the conductive agent, 1.0%-2.3% of the binder and 0.3%-1.6% of the polymerized monomer. It is advisable to adjust the amount of each component within the above range to ensure the amount of polymerized monomer introduced, which is conducive to improving the electrochemical performance of the battery.
[0057] Specifically, the total amount of negative electrode active material, conductive agent, binder and polymerized monomer is 100%, and the amount of solvent added during the homogenization process is not included. The mass fraction of negative electrode active material can be 94%, 95%, 96%, 97%, etc.; the mass fraction of conductive agent can be 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, etc.; the mass fraction of binder can be 1.0%, 1.3%, 1.5%, 1.8%, 2.0%, 2.3%, etc.; the mass fraction of polymerized monomer can be 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, 1.6%, etc.
[0058] In some embodiments, the negative electrode active material is graphite (such as artificial graphite), but is not limited thereto. The conductive agent is selected from at least one of conductive carbon black SP, carbon nanotubes (CNTs) and graphene (GR), and the conductive agent can be any one or more of the above.
[0059] In some embodiments, the binder includes, by mass fraction, 0.5%-1.5% carboxymethyl cellulose (CMC), 0%-1.3% polyacrylic acid (PAA) and 0.2%-0.8% styrene butadiene rubber (SBR). The above three binders are used to improve the adhesion effect of the negative electrode active coating on the negative electrode current collector. Specifically, the mass fraction of carboxymethyl cellulose (CMC) can be 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, etc.; the mass fraction of polyacrylic acid (PAA) can be 0.0%, 0.3%, 0.5%, 0.8%, 1.0%, 1.3%, etc.; the mass fraction of styrene butadiene rubber (SBR can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, etc.
[0060] In some embodiments, the preparation process of the negative electrode slurry includes: firstly mixing carboxymethyl cellulose, polyacrylic acid and water to obtain a glue solution, then mixing the glue solution with a conductive agent and a negative electrode active material in sequence, and then mixing with styrene-butadiene rubber and a polymerized monomer, and adjusting the mixing order and using a high-speed dispersion method during the mixing process to make the raw materials uniformly mixed. After the mixing is completed, the negative electrode slurry is coated on the negative electrode current collector, and the coating double-sided surface density of the negative electrode slurry is controlled to be 100-300g / m 2 (For example, it can be 100g / m 2 , 150g / m 2 , 200g / m 2 , 250g / m 2 , 300g / m 2 The negative electrode current collector used may be a copper foil with a thickness of 4 μm-12 μm, and the specific thickness may be 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, etc.
[0061] S2. Providing an electrolyte containing an initiator
[0062] The mass fraction of the initiator in the electrolyte is 0.05%-2.0%, the mass fraction of the basic lithium salt electrolyte is 98-99.95%, and the basic lithium salt electrolyte contains 1%-3% of an unsaturated olefin additive. Specifically, the mass fraction of the initiator in the electrolyte can be 0.05%, 0.10%, 0.30%, 0.50%, 0.80%, 1.00%, 1.30%, 1.50%, 1.80%, 2.00%, etc.; the mass fraction of the basic lithium salt electrolyte can be 98.00%, 98.20%, 98.50%, 98.70%, 99.00%, 99.20%, 99.50%, 99.70%, 99.90%, 99.95%, etc.; the mass fraction of the unsaturated olefinic additive in the basic lithium salt electrolyte can be 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, etc.
[0063] In some embodiments, the initiator is selected from at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (AVBN), dicumyl peroxide (DCP) and benzoyl peroxide (BPO), and the initiator can be any one or more of the above.
[0064] In some embodiments, in addition to the initiator, the electrolyte further contains a lithium salt, a solvent and an additive, and the specific types and amounts of the raw materials can refer to the prior art. The lithium salt can be LiPF6, and the concentration of the lithium salt is 0.8mol / L-1.2mol / L, such as 0.8mol / L, 1.0mol / L, 1.2mol / L, etc.
[0065] Furthermore, the solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the volume ratio of ethylene carbonate to ethyl methyl carbonate is (2-4):(6-8), such as 2:8, 3:7, 4:6, etc. On the premise of satisfying the ratio of ethylene carbonate (EC) to ethyl methyl carbonate (EMC), the total amount of the solvent is adjusted to make the concentrations of other components meet the requirements.
[0066] Furthermore, the additives include vinylene carbonate (VC) and propylene sulfite (PS), the mass fraction of vinylene carbonate is 0.8%-1.2%, and the mass fraction of propylene sulfite is 1.5%-2.5%. Specifically, the mass fraction of vinylene carbonate can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, etc.; the mass fraction of propylene sulfite can be 1.5%, 1.8%, 2.0%, 2.3%, 2.5%, etc.
[0067] S3, provide positive electrode sheet and diaphragm
[0068] The types of the positive electrode sheet and the separator are not limited, and may be common positive electrode sheets and separators for lithium batteries. For example, the separator may be a PP separator, a PE separator, a ceramic separator, and the like.
[0069] In some embodiments, the preparation process of the positive electrode sheet includes: mixing the positive electrode active material, the conductive agent and the binder to obtain a positive electrode slurry, applying the positive electrode slurry on the positive electrode collector and drying it, removing the solvent for the slurry, and preparing the positive electrode sheet. The positive electrode active material is selected from at least one of lithium iron phosphate, ternary nickel cobalt manganese, lithium manganese iron phosphate, lithium nickel manganate and lithium manganate. The positive electrode active material can be any one or more of the above; the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene, and the conductive agent can be any one or more of the above; the binder is selected from at least one of polyvinylidene fluoride, polyacrylic acid and polyacrylonitrile, and the binder can be any one or more of the above.
[0070] Furthermore, when preparing the positive electrode slurry, the mass proportion of the positive electrode active material is 96.8%-97.3%, the mass proportion of the conductive agent is 1.8%-2.2%, and the mass proportion of the binder is 0.8%-1.2%. The ratio of the positive electrode active material, the conductive agent, and the binder is preferably within the above range to further improve the electrochemical performance of the battery. Specifically, the mass proportion of the positive electrode active material can be 96.8%, 96.9%, 97.0%, 97.1%, 97.2%, 97.3%, etc.; the mass proportion of the conductive agent can be 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, etc.; the mass proportion of the binder can be 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, etc.
[0071] S4, assembly, injection, formation, polymerization
[0072] Assemble the negative electrode sheet, the positive electrode sheet and the separator to obtain a battery cell; inject the electrolyte into the battery cell, and heat and polymerize after formation. The assembly method of the battery cell is not limited, and it can be an existing lithium battery cell assembly method. The separator is located between the positive electrode sheet and the negative electrode sheet, and the battery cell can be prepared by lamination or winding.
[0073] Furthermore, the formation method is not limited, and it can be a formation process at room temperature, and the formation temperature can be 20°C-30°C, such as 20°C, 25°C, 30°C, etc.
[0074] Furthermore, during the temperature-raising polymerization process, the polymerization temperature is controlled to be 45°C-60°C, and the polymerization time is 6h-8h. Under the condition of thermal initiation, the polymerization monomers can be fully reacted to form a semi-solid electrolyte. Specifically, the polymerization temperature can be 45°C, 50°C, 55°C, 60°C, etc., and the polymerization time can be 6h, 7h, 8h, etc.
[0075] It should be noted that the embodiment of the present invention adds polymerization monomers during the negative electrode slurry mixing process, and adopts a method of first forming and then high-temperature thermal polymerization, which does not affect the full wetting and film formation of the electrolyte during the aging and formation stages, so that the uniformity of its in-situ curing and film formation stability are significantly improved, so the battery's rate performance is not deteriorated and the high-temperature performance is significantly improved.
[0076] The embodiment of the present invention also provides an in-situ cured lithium battery, which is prepared by the preparation method provided by the embodiment of the present invention, has a gel semi-solid electrolyte, has high in-situ curing uniformity, and can improve the high temperature performance of the battery without degrading the rate performance.
[0077] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0078] Example 1
[0079] This embodiment provides a method for preparing an in-situ cured lithium battery, the steps are as follows:
[0080] (1) Provide negative electrode sheet
[0081] Negative electrode slurry: CMC and PAA are dissolved in deionized water to form a gel solution, and a conductive agent SP is added to the gel solution to form a conductive gel during high-speed dispersion (rotation speed is 500 rpm, the same below). Active material graphite is then added to the conductive gel, and the viscosity is adjusted after high-speed dispersion (rotation speed is 4500 rpm, the same below). Finally, SBR and polymerization monomer 1 are added and dispersed evenly to form a negative electrode slurry.
[0082] The polymerizable monomer 1 is a polyamide monomer containing a fluorinated alkyl group, and the chemical formula is as follows:
[0083]
[0084] Table 1 Mass ratio of each component of negative electrode slurry in Example 1
[0085] Material Name Ingredient ratio / % graphite 95.50% SP 1.90% CMC 0.50% PAA 0.80% SBR 0.50% Polymerization monomer 1 0.80%
[0086] The negative electrode slurry was coated on both sides of the copper foil with a thickness of 8 μm, and the coating double-sided surface density was controlled to be 165 g / m 2 The rolling thickness was controlled at 126 μm, and after slitting and punching, the negative electrode sheet was dried at 95°C for 24 hours.
[0087] (2) Providing an electrolyte containing an initiator
[0088] After mixing EC, EMC and LiPF6, VC, PS and AIBN are added to obtain an electrolyte.
[0089] In the electrolyte, the concentration of LiPF6 is 1.0M, the volume ratio EC / EMC is 3 / 7, the mass fraction of VC is 1.0%, the mass fraction of PS is 2.0%, and the mass fraction of AIBN is 1.0%.
[0090] (3) Provide positive electrode sheets and diaphragms
[0091] Positive electrode slurry: 97% of commercially available lithium iron phosphate active material, 2% of conductive agent carbon black and 1% of binder polyvinylidene fluoride were mixed and homogenized in proportion to obtain positive electrode slurry.
[0092] The positive electrode slurry was coated on both sides of the 16 μm aluminum foil, and the coating double-sided surface density was controlled to be 318 g / m 2 The rolling thickness was controlled at 151 μm, and after slitting and punching, the positive electrode sheet was dried at 95°C for 24 hours.
[0093] The diaphragm used is a PP diaphragm with a thickness of 20 μm.
[0094] (4) Assembly, injection, formation, polymerization
[0095] The negative electrode sheet, the positive electrode sheet and the separator are assembled and a battery cell is obtained through a lamination process; the electrolyte is injected into the battery cell, aged at 25°C for 48 hours, then formed at 25°C, and finally placed at 45°C for 24 hours to complete polymerization and aging.
[0096] The formation process is as follows: ① stand for 5 minutes; ② constant current charging for 300 minutes, current 0.02C, protection voltage 3.8V; ③ stand for 5 minutes, constant current charging for 300 minutes, current 0.1C, protection voltage 3.8V; ④ end.
[0097] Example 2
[0098] This embodiment provides a method for preparing an in-situ cured lithium battery, the steps are as follows:
[0099] (1) Provide negative electrode sheet
[0100] The only difference from Example 1 is that the mass proportions of the components are as shown in Table 2.
[0101] Table 2 Mass ratio of each component of negative electrode slurry in Example 2
[0102] Material Name Ingredient ratio / % graphite 95.50% SP 1.90% CMC 0.50% PAA 1.30% SBR 0.50% Polymerization monomer 1 0.30%
[0103] (2) Providing an electrolyte containing an initiator
[0104] Same as Example 1.
[0105] (3) Provide positive electrode sheets and diaphragms
[0106] Same as Example 1.
[0107] (4) Assembly, injection, formation, polymerization
[0108] Same as Example 1.
[0109] Example 3
[0110] This embodiment provides a method for preparing an in-situ solidified lithium battery, the steps of which are as follows: (1) providing a negative electrode sheet;
[0111] The only difference from Example 1 is that the mass proportions of the components are as shown in Table 3.
[0112] Table 3 Mass ratio of each component of negative electrode slurry in Example 3
[0113] Material Name Ingredient ratio / % graphite 95.50% SP 1.90% CMC 0.50% PAA 1.00% SBR 0.50% Polymerization monomer 1 0.60%
[0114] (2) Providing an electrolyte containing an initiator
[0115] Same as Example 1.
[0116] (3) Provide positive electrode sheets and diaphragms
[0117] Same as Example 1.
[0118] (4) Assembly, injection, formation, polymerization
[0119] Same as Example 1.
[0120] Example 4
[0121] This embodiment provides a method for preparing an in-situ solidified lithium battery, the steps of which are as follows: (1) providing a negative electrode sheet;
[0122] The only difference from Example 1 is that the mass proportions of the components are as shown in Table 4.
[0123] Table 4 Mass ratio of each component of negative electrode slurry in Example 4
[0124] Material Name Ingredient ratio / % graphite 95.50% SP 1.90% CMC 0.50% PAA 0.00% SBR 0.50% Polymerization monomer 1 1.60%
[0125] (2) Providing an electrolyte containing an initiator
[0126] Same as Example 1.
[0127] (3) Provide positive electrode sheets and diaphragms
[0128] Same as Example 1.
[0129] (4) Assembly, injection, formation, polymerization
[0130] Same as Example 1.
[0131] Example 5
[0132] This embodiment provides a method for preparing an in-situ cured lithium battery, the steps are as follows:
[0133] (1) Provide negative electrode sheet
[0134] The only difference from Example 1 is that the polymerizable monomer used is polymerizable monomer 2 (a polyacrylate monomer containing a fluorinated alkyl group), and its chemical formula is as follows:
[0135]
[0136] The mass proportions of the various components are shown in Table 5 (same as Example 1, only the monomer types are replaced).
[0137] Table 5 Mass ratio of each component of negative electrode slurry in Example 5
[0138] Material Name Ingredient ratio / % graphite 95.50% SP 1.90% CMC 0.50% PAA 0.80% SBR 0.50% Polymerization monomer 2 0.80%
[0139] (2) Providing an electrolyte containing an initiator
[0140] Same as Example 1.
[0141] (3) Provide positive electrode sheets and diaphragms
[0142] Same as Example 1.
[0143] (4) Assembly, injection, formation, polymerization
[0144] Same as Example 1.
[0145] Example 6
[0146] The only difference from Example 1 is that the content of the initiator in step (2) is 0.05%.
[0147] Example 7
[0148] The only difference from Example 1 is that the content of the initiator in step (2) is 2%.
[0149] Example 8
[0150] The only difference from Example 1 is that the polymerization temperature after formation in step (4) is 55°C.
[0151] Example 9
[0152] The only difference from Example 1 is that the polymerization temperature after formation in step (4) is 60°C.
[0153] Example 10
[0154] The only difference from Example 1 is that the polymerization time after formation in step (4) is 12 hours.
[0155] Embodiment 11
[0156] The only difference from Example 1 is that the polymerization time after formation in step (4) is 48 hours.
[0157] Comparative Example 1
[0158] This comparative example provides a method for preparing a lithium ion battery, the steps are as follows:
[0159] (1) Provide negative electrode sheet
[0160] The only difference from Example 1 is that no polymerization monomer 1 is added, and the proportions of the components are shown in Table 6.
[0161] Table 6 Mass ratio of each component of negative electrode slurry in comparative example 1
[0162]
[0163]
[0164] (2) Providing an electrolyte that does not contain an initiator
[0165] After mixing EC, EMC and LiPF6, VC and PS are added to obtain an electrolyte.
[0166] In the electrolyte, the concentration of LiPF6 is 1.0M, the volume ratio EC / EMC is 3 / 7, the mass fraction of VC is 1.0%, and the mass fraction of PS is 2.0%.
[0167] (3) Provide positive electrode sheets and diaphragms
[0168] Same as Example 1.
[0169] (4) Assembly, injection, formation, polymerization
[0170] The negative electrode sheet, positive electrode sheet and separator are assembled and a battery cell is obtained through a lamination process; the electrolyte is injected into the battery cell, formed at 25°C, and then placed at 45°C for 24 hours to complete aging.
[0171] The formation process is the same as that in Example 1.
[0172] Comparative Example 2
[0173] The only difference from Example 1 is that the polymerizable monomer in step (1) is replaced by an equal amount of polymerizable monomer 3 (aromatic polycarbonate), and the chemical formula is as follows:
[0174]
[0175] Comparative Example 3
[0176] The only difference from Example 1 is that the polymerizable monomer in step (1) is replaced by an equal amount of polymerizable monomer 4 (polyethylene terephthalate), and the chemical formula is as follows:
[0177]
[0178] Test Example 1
[0179] The capacity retention rate and cycle performance of the batteries prepared in the examples and comparative examples were tested, and the results are shown in Table 7.
[0180] Test steps and conditions:
[0181] (1) 25℃ rate discharge: charge at 0.5C constant current and constant voltage at 25℃, and discharge at 0.5C constant current for three cycles to fix the capacity; then charge at 0.5C constant current and constant voltage to 3.65V, cut off current 0.05C, leave for 30 minutes, and then discharge at 2.0C constant current to 2.5V, and then end.
[0182] (2) 55℃ cycle: charge at 0.5C constant current and constant voltage at 25℃, and discharge at 0.5C constant current for three cycles to constant capacity; then heat to 55℃ and leave for 30 minutes, charge at 1.0C constant current and constant voltage to 3.65V, cut off current 0.05C, leave for 30 minutes, discharge at 1.0C constant current to 2.5V, cycle 3000 times and stop testing.
[0183] Table 7 Capacity retention and cycle performance of the batteries prepared in the examples and comparative examples
[0184]
[0185] It can be seen that the rate performance and cycle performance of the batteries prepared in Examples 1-11 are more excellent than those in the comparative examples.
[0186] By comparing Examples 1-4, it can be seen that the amount of polymerization monomer used in Example 1 is optimal; by comparing Example 1 and Example 5, it can be seen that the monomer type in Example 1 can improve the rate performance and cycle performance of the battery more than that in Example 5.
[0187] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an in-situ cured lithium battery, characterized in that: include: Providing positive electrode sheets, separators and electrolytes containing initiators; A negative electrode active material, a conductive agent, a binder and a polymerizable monomer are mixed to obtain a negative electrode slurry, and the negative electrode slurry is coated on a negative electrode current collector and dried to prepare a negative electrode plate; wherein the polymerizable monomer is a fluorinated alkyl-modified polyamide monomer or a fluorinated alkyl-modified polyacrylate monomer; Assembling the negative electrode sheet, the positive electrode sheet and the separator to obtain a battery cell; The electrolyte is injected into the battery core, and after being formed, the temperature is raised and polymerized.
2. The preparation method according to claim 1, characterized in that: The general formula of the fluorinated alkyl modified polyamide monomer is: In the formula, R is a fluoroalkyl group, and the carbon atom content in R is 1 to 20; 2≤n1≤10, 1≤n2≤20; Preferably, R is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-.
3. The preparation method according to claim 1, characterized in that: The general formula of the fluorinated alkyl modified polyacrylate monomer is: In the formula, R1 is a fluoroalkyl group, and the carbon atom content in R1 is 1 to 20; R2 is H or CH3-, 1≤n≤20; Preferably, R1 is selected from at least one of CF3CH2-, C2F5CH2-, H(CF2)2CH2- and nC3F7CH2-.
4. The preparation method according to any one of claims 1 to 3, characterized in that When preparing the negative electrode slurry, the mass fractions of the raw materials are as follows: 94%-97% of negative electrode active material, 1.5%-2.5% of conductive agent, 1.0%-2.3% of binder and 0.3%-1.6% of polymerized monomer.
5. The preparation method according to claim 4, characterized in that: The negative electrode active material is graphite; And / or, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene; And / or, by mass fraction, the binder comprises 0.5%-1.5% carboxymethyl cellulose, 0%-1.3% polyacrylic acid and 0.2%-0.8% styrene-butadiene rubber; And / or, the preparation process of the negative electrode slurry comprises: firstly mixing carboxymethyl cellulose, polyacrylic acid and water to obtain a glue solution, then sequentially mixing the glue solution with the conductive agent and the negative electrode active material, and then mixing with the styrene-butadiene rubber and the polymerized monomer; And / or, the negative electrode current collector is a copper foil with a thickness of 4 μm-12 μm; And / or, the coating double-sided density of the negative electrode slurry is 100-300g / m 2 .
6. The preparation method according to claim 1, characterized in that: The mass fraction of the initiator in the electrolyte is 0.05%-2.0%, the mass fraction of the basic lithium salt electrolyte is 98-99.95%, and the basic lithium salt electrolyte contains 1%-3% of an unsaturated olefin additive; And / or, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dicumyl peroxide and benzoyl peroxide.
7. The preparation method according to claim 6, characterized in that: The basic lithium salt electrolyte comprises a lithium salt, a solvent and an additive; Preferably, the lithium salt is LiPF6, and the concentration of the lithium salt is 0.8 mol / L-1.2 mol / L; Preferably, the additive comprises vinylene carbonate and propylene sulfite, the mass fraction of vinylene carbonate is 0.8%-1.2%, and the mass fraction of propylene sulfite is 1.5%-2.5%; Preferably, the solvent comprises ethylene carbonate and ethyl methyl carbonate, and the volume ratio of ethylene carbonate to ethyl methyl carbonate is (2-4):(6-8).
8. The preparation method according to claim 1, characterized in that: During the polymerization process, the polymerization temperature is controlled at 45°C-60°C and the polymerization time is 6h-8h; And / or, the formation temperature is 20°C-30°C.
9. The preparation method according to claim 1, characterized in that: The preparation process of the positive electrode sheet includes: mixing a positive electrode active material, a conductive agent and a binder to obtain a positive electrode slurry, applying the positive electrode slurry on a positive electrode collector and drying the positive electrode sheet; Preferably, when preparing the positive electrode slurry, the mass proportion of the positive electrode active material is 96.8%-97.3%, the mass proportion of the conductive agent is 1.8%-2.2%, and the mass proportion of the binder is 0.8%-1.2%; Preferably, the positive electrode active material is selected from at least one of lithium iron phosphate, ternary nickel cobalt manganese, lithium manganese iron phosphate, lithium nickel manganate and lithium manganate; Preferably, the conductive agent is selected from at least one of conductive carbon black, carbon nanotubes and graphene; Preferably, the binder is selected from at least one of polyvinylidene fluoride, polyacrylic acid and polyacrylonitrile.
10. An in-situ cured lithium battery, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.
Citation Information
Cited By
Electrode assembly with solid electrolyte, battery cell and manufacturing method
CN121011709A